The Influence of Personal Selling, Digital Marketing, and Promotion on the Purchase Decision of Koota Indonesia Products at PT. Aplikasi Cipta Mandiri in Jakarta - Rini, Martriasih Sivia; Permana, Deni (Indonesian Journal of Social Science Research, 2026)
The purchase of products in both large and small enterprises is significantly influenced by the strategic approaches implemented by the company to enhance sales. This study was conducted using a quantitative method, with the primary data collection technique involving the distribution of questionnaires to 60 customers of PT. Aplikasi Cipta Mandiri. The objective of this research is to analyze the influence of Personal Selling, Digital Marketing, and Promotion on the purchase decisions of Koota Indonesia products at PT. Aplikasi Cipta Mandiri in Jakarta. This study utilizes an associative quantitative design to examine the relationships between variables. Data analysis involved instrument validity and reliability testing, normality testing, and multiple linear regression analysis performed via SPSS version 25. The results indicate that the Digital Marketing variable (X2) has a substantial, direct, and significant influence on Purchase Decisions, with a significance value of 0.000 < 0.05 and a t_value of 6.711 > 1.673. The conclusion of this research is that Personal Selling, Digital Marketing, and Promotion collectively exert a positive and significant influence on the purchase decisions of Koota Indonesia products at PT. Aplikasi Cipta Mandiri, with a calculated F-value of 56.604. The simultaneous contribution (R-Square) of these variables is 73.9%, while the remaining 26.1% is influenced by other factors not examined in this study.